The effect of supplemental oral phosphate on the bone mineral changes during prolonged bed rest - Hulley, Stephen B. (1971)
Five healthy young men were studied during 24-30 wk of continuous bed rest. During the first 12 wk of bed rest, untreated subjects increased calcium excretion in the urine by 109 mg/day and in the feces by 147 mg/day. The rate of total body calcium loss was 0.5-0.7% per month. Losses of central calcaneus mineral, assessed by gamma ray transmission scanning, occurred at a tenfold higher rate, whereas the mineral content of the radius did not change. Changes in phosphorus balance resembled the calcium pattern, and increased excretion of nitrogen and hydroxyproline also occurred during bed rest. Upon reambulation, the subjects' calcium balance became positive in 1 month and recovery of their calcaneus mineral was complete within 10-20 wk. Treatment with potassium phosphate supplements (1327 mg P/day) entirely prevented the hypercalciuria of bed rest, but fecal calcium tended to increase. During the first 12 wk, calcium balance was slightly less negative (mean - 193 mg/day) than during bed rest without added phosphate (mean - 267 mg/day). This effect was not seen during the second 12 wk of bed rest. The patterns of magnesium excretion were similar to those of calcium. Fecal and urinary phosphorus excretions were doubled, and phosphorus balance became positive (+ 113 mg/day). Mineral loss from the central calcaneus was similar to that of untreated subjects. It is concluded that this form of phosphate supplementation reduces urinary calcium excretion but does not prevent bone loss during bed rest.